Faktor Kesulitan Mahasiswa Program Studi Bahasa Korea Sekolah Vokasi UGM dalam Menjawab Soal TEVocS - Alfelia Nugky Permatasari; Yuni Wachid Asrori (JLA (Jurnal Lingua Applicata), 2019)
Decree of Dean of Universitas Gadjah Mada Vocational School no. 10/UN1.SV/SK/2017 regarding graduation requirements for Universitas Gadjah Mada Vocational School students requires a minimum TEVocS score of 60 as one of the graduation requirements. This requirement burdens students, especially the ones other than English Language study program. To be able to graduate, a number of students even had to repeat their TEVocS until they get the required score. This study aims to identify the factors causing the difficulties of UGM Vocational School Korean Language study program students in answering TEVocS questions.This research used quantitative and qualitative approaches. A total of 44 Korean Language study program students became the objects of this study. Students were asked to complete TEVocS simulation and evaluate their performance, specifically related to the factors that caused them feel difficult in answering TEVocS questions. The evaluation was done using questionnaire. The finding shows that, in general, almost all Korean Language study program students found it difficult to answer TEVocS questions. Almost all Korean Language study program students admitted that they had difficulties in both listening and speaking sections of TEVocS. These difficulties were caused by a number of factors.